Procesy zarządzania wiedzą jako wyzwanie gospodarki opartej na wiedzy - Filip Tużnik (Studia i Materiały)
The article concerns the idea of knowledge and its innovative potential in the knowledge-based economy. The processes related to the knowledge transfer and knowledge management are often considered as factors determining the success in innovativeness. Knowledge management is also an important issue in inter-organizational cooperation since it considerably helps in the development of new technological solutions. The article provides research results on knowledge management conducted among enterprises and scientific units involved in cooperation under R&D projects co-financed by the Polish Federation of Engineering Associations and the National Centre for Research and Development.